2014
DOI: 10.3389/fmicb.2014.00526
|View full text |Cite
|
Sign up to set email alerts
|

Oligotyping reveals differences between gut microbiomes of free-ranging sympatric Namibian carnivores (Acinonyx jubatus, Canis mesomelas) on a bacterial species-like level

Abstract: Recent gut microbiome studies in model organisms emphasize the effects of intrinsic and extrinsic factors on the variation of the bacterial composition and its impact on the overall health status of the host. Species occurring in the same habitat might share a similar microbiome, especially if they overlap in ecological and behavioral traits. So far, the natural variation in microbiomes of free-ranging wildlife species has not been thoroughly investigated. The few existing studies exploring microbiomes through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 70 publications
2
37
0
Order By: Relevance
“…However, the observed similarities between the oligotypes from sewage and those from feces of swine, cats, and dogs suggest that any indicators developed should be tested thoroughly against feces from a wider selection of these hosts to ensure their specificity or high degree of preference for sewage. Although the differentiation of animal sources was not the focus of this study, similarities (shared oligotypes) were common among hosts with similar diets and/or physiologies, such as humans (sewage) and swine or deer and cows, as has been observed in other studies (10,25,45). This suggests that a more comprehensive sampling effort with respect to particular animals of interest would also yield hostspecific oligotypes for tracking animal fecal pollution.…”
Section: Next-generation Sequencing Approaches To Identifying Alternamentioning
confidence: 72%
See 1 more Smart Citation
“…However, the observed similarities between the oligotypes from sewage and those from feces of swine, cats, and dogs suggest that any indicators developed should be tested thoroughly against feces from a wider selection of these hosts to ensure their specificity or high degree of preference for sewage. Although the differentiation of animal sources was not the focus of this study, similarities (shared oligotypes) were common among hosts with similar diets and/or physiologies, such as humans (sewage) and swine or deer and cows, as has been observed in other studies (10,25,45). This suggests that a more comprehensive sampling effort with respect to particular animals of interest would also yield hostspecific oligotypes for tracking animal fecal pollution.…”
Section: Next-generation Sequencing Approaches To Identifying Alternamentioning
confidence: 72%
“…Our recent analysis of fecal community profiles using this approach with sequences that mapped to the genus Blautia revealed a high degree of host preference and host specificity for both humans and other animals at the oligotype level (35). Another recent study by Menke et al also demonstrated the efficacy of Blautia at distinguishing two free-ranging sympatric carnivore host species (45). Our current study expanded upon this effort and examined eight fecal taxa, in addition to Blautia (32,35) and the widely studied Bacteroides (8,13,15,16,44), that are relatively unexplored in terms of source tracking to determine the potential of each of these taxa to provide novel targets for use as alternative indicators.…”
Section: Next-generation Sequencing Approaches To Identifying Alternamentioning
confidence: 95%
“…Firmicutes is the only phylum universally shared in mammals (Ley et al. ) and in some carnivore species and human Firmicutes has a relative abundance of >60% (Menke et al., , ).…”
Section: Discussionmentioning
confidence: 99%
“…The laboratory work including DNA extraction, PCR protocol, purification, library generation and sequencing was as described in detail by Menke et al. (). All individuals were run in duplicate in independent PCRs labelled with different barcodes and were processed for library preparation and paired‐end sequencing in a single run of next‐generation sequencing (NGS) Illumina ® MiSeq.…”
Section: Methodsmentioning
confidence: 99%